Expansion of a specific plasmodium falciparum PfMDR1 Haplotype in southeast Asia with increased substrate transport - Calçada, Carla Sofia Martins (2020)
Artemisinin-based combination therapies (ACTs) have been vital in reducing malaria mortality rates since the 2000s. Their efficacy, however, is threatened by the emergence and spread of artemisinin resistance in Southeast Asia. The Plasmodium falciparum multidrug resistance protein 1 (PfMDR1) transporter plays a central role in parasite resistance to ACT partner drugs through gene copy number variations (CNV) and/or single nucleotide polymorphisms (SNPs). Using genomic epidemiology, we show that multiple pfmdr1 copies encoding the N86 and 184F haplotype are prevalent across Southeast Asia. Applying genome editing tools on the Southeast Asian Dd2 strain and using a surrogate assay to measure transporter activity in infected red blood cells, we demonstrate that parasites harboring multicopy N86/184F PfMDR1 have a higher Fluo-4 transport capacity compared with those expressing the wild-type N86/Y184 haplotype. Multicopy N86/184F PfMDR1 is also associated with decreased parasite susceptibility to lumefantrine. These findings provide evidence of the geographic selection and expansion of specific multicopy PfMDR1 haplotypes associated with multidrug resistance in Southeast Asia.IMPORTANCE Global efforts to eliminate malaria depend on the continued success of artemisinin-based combination therapies (ACTs) that target Plasmodium asexual blood-stage parasites. Resistance to ACTs, however, has emerged, creating the need to define the underlying mechanisms. Mutations in the P. falciparum multidrug resistance protein 1 (PfMDR1) transporter constitute an important determinant of resistance. Applying gene editing tools combined with an analysis of a public database containing thousands of parasite genomes, we show geographic selection and expansion of a pfmdr1 gene amplification encoding the N86/184F haplotype in Southeast Asia. Parasites expressing this PfMDR1 variant possess a higher transport capacity that modulates their responses to antimalarials. These data could help tailor and optimize antimalarial drug usage in different regions where malaria is endemic by taking into account the regional prevalence of pfmdr1 polymorphisms.